Pacific Island Countries : Possible Common Currency Arrangement - Orsmond, David (IMF Working Papers; Working Paper ;, 2006)
This paper examines the potential advantages and disadvantages of adopting a common currency arrangement among the six IMF member Pacific island countries that have their own national currency. These countries are Fiji, Papua New Guinea, Samoa, Solomon Islands, Tonga, and Vanuatu. The study explains that the present exchange rate regimes-comprising pegging to a basket of currencies for five countries and the floating arrangement for Papua New Guinea-have generally succeeded in avoiding inflationary, balance of payments, external debt, and financial system problems. The study concludes that adopting a common currency in the Pacific would require greater convergence of domestic policies and substantial strengthening of regional policies, which would take time to achieve.